What drives students’ successful reuse of online learning in higher education? A case of Google Classroom - Hussein, Mahmood H.; Ow, Siew Hock; Al-Azawei, Ahmed; Ibrahim, Ishaq (Australasian Journal of Educational Technology, 2022)
This study aims at proposing an integrated model based on the technology acceptance model, the information system success model, cognitive load theory, and personal characteristics to predict students' continued intention to reuse Google Classroom in the context of a developing country. To achieve this, we conducted quantitative research, empirically identifying the factors that could affect the continued intention of higher education students to reuse Google Classroom. Overall, 233 higher education students voluntarily participated in this research. Structural equation modelling was adopted as the method of analysis. The results showed that cognitive load significantly influenced perceived ease of use, whereas it had no impact on perceived usefulness or satisfaction. Furthermore, all personal characteristics significantly affected perceived ease of use. The outcomes likewise revealed that perceived usefulness, perceived ease of use, and satisfaction had a significant and positive effect on students’ continued intention to reuse Google Classroom. However, to enhance the generalisability of the findings, further research with a larger research sample is required. In addition, the predictability power of the proposed model could be improved by considering the role of other factors, such as engagement and learning effectiveness. Implications for practice or policy: To ensure successful reuse of learning management systems (LMSs), course leaders should pay attention to students' perceptions. LMS developers should place greater emphasis on students’ individual differences, to maximise the effectiveness of LMS implementation. Instructors should ensure that the learning material does not require a high cognitive load, as this could produce learning fatigue. Educational institutions should consider students' satisfaction with particular learning technology, as this would affect students’ willingness to reuse it.